PENGARUH ENERGI CHALLENGE BOARD GAME TERHADAP KEMAMPUAN MENGEVALUASI KONSEP ENERGI PADA SISWA KELAS V SB KAMPUNG BARU MALAYSIA - Nabila, Miranda; Suci Perwita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Energy Challenge Board Game on fifth-grade students’ ability to evaluate energy concepts at SB Kampung Baru, Malaysia. The participants consisted of 21 students. The research employed a one-group pretest–posttest experimental design. The instrument used was an energy concept evaluation test comprising 15 multiple-choice items and 5 essay questions. Data were analyzed using a t-test to examine differences between the pretest and posttest scores. The results indicated that the significance value was below 0.05, leading to the acceptance of Ha and rejection of H0, which means that the Energy Challenge Board Game had a significant effect on students’ evaluation abilities. The increase in the posttest mean score compared to the pretest further demonstrates improvement in students’ skills after the implementation of the board game. These findings suggest that the Energy Challenge Board Game positively contributes to the enhancement of students’ ability to evaluate energy concepts in the fifth grade at SB Kampung Baru, Malaysia.